Profil lipid pada wanita dengan sindrom koroner akut - ., Ronaldi; Adriana, Ike; Rotty, Monique; Lefrandt, Reginald L.; Panda, Agnes L. (Jurnal Biomedik : JBM, 2016)
Abstract: Females with acute coronary syndrome (ACS) display different characteristics from the opposite gender. Currently, only limited data were available regarding the characteristic of ACS in females, especially in Manado. This study aimed to obtain the lipid profile of females with ACS at Prof. Dr. R. D. Kandou Hospital Manado in 2012-2013. This was a descriptive retrospective study with a cross sectional design. Subjects were all female patients with ACS who were admitted to Prof. Dr. R. D. Kandou Hospital Manado from January 2012 to December 2013. Data were collected based on the medical record. Exclusion criteria included incomplete data and non-ACS as the main diagnosis. There were 81 women as subjects in this study. The mean age was 61.59±10.78 years. Unstable angina pectoris, non-ST elevation myocardial infarction, ST elevation myocardial infarction were found in 38 (46.9%), 15 (18.5%), and 28 (34.6%) patients consecutively. Mean value of total cholesterol, low density lipoprotein (LDL), high density lipoprotein (HDL), and trygliserida levels were as follows: 218.17±48.88, 145.91±47.30, 39.72±15.99, and 153±65.55 mg/dl. High level of total cholesterol, LDL, and trygliserida were found in 52 (64.2%), 50 (61.7%), 14 (17.3%) patients consecutively meanwhile low HDL level was found in 51(63%) patients. Diabetes mellitus and hypertension were found in 24 (29.6%) and 58 (71.6%) patients. The mean length of stay was 8.44±4.36 days.Keywords: female, lipid profile, acute coronary syndromeAbstrak: Wanita dengan sindrom koroner akut (SKA) menampilkan karakteristik yang berbeda daripada laki-laki dengan SKA. Sampai saat ini, masih tersedia sedikit data mengenai karakteristik SKA pada wanita. Penelitian ini bertujuan mendapatkan gambaran profil lipid pada wanita dengan SKA yang dirawat di RSUP Prof. Dr. R. D. Kandou. Jenis penelitian ini deskriptif retrospektif dengan desain potong lintang. Subyek penelitian ialah pasien wanita dengan SKA yang dirawat di RSUP Prof. Dr. R. D. Kandou, Manado dari Januari 2012-Desember 2013. Data dikumpulkan dari rekam medis. Kriteria eksklusi meliputi data yang tidak lengkap dan diagnosis selain SKA sebagai diagnosis utama. Hasil penelitian mendapatkan subyek 81 pasien wanita dengan usia rata-rata 61,59±10,78 tahun. Angina pektoris tak stabil ditemukan pada 38 pasien (46,9%), non-ST segment elevation myocardial infarction pada 15 pasien (18,5%), dan ST segment elevation myocardial infarction pada 28 pasien (34,6%). Kadar rerata kolesterol total, low density lipoprotein (LDL), high density lipoprotein (HDL), dan trigliserida ialah berturut-turut 218,17±48,88, 145,91±47,30, 39,72±15,99, dan 153±65,55 mg/dl. Kadar kolesterol total, LDL, trigliserida yang tinggi ditemukan berturut-turut pada 52 pasien (64,2%), 50 pasien (61,7%), dan 14 pasien (17,3%) sedangkan kadar HDL yang rendah ditemukan pada 51 pasien (63%). Diabetes melitus dan hipertensi ditemukan pada 24 pasien (29,6%) dan 58 pasien (71,6%). Rerata lama perawatan di rumah sakit ialah 8,44±4,36 hari.Kata kunci: wanita, profil lipid, sindrom koroner akut